Correlation between multi-factor phase diagrams and complex electrocaloric behaviors in PNZST antiferroelectric ceramic system - Junjie Li; Ruowei Yin; Jianting Li; Xiaopo Su; Yanjing Su; Lijie Qiao; Yang Bai (Journal of Advanced Ceramics, 2023)
Ferroelectric (FE) phase transition with a large polarization change benefits to generate large electrocaloric (EC) effect for solid-sate and zero-carbon cooling application. However, most EC studies only focus on the single-physical factor associated phase transition. Herein, we initiated a comprehensive discussion on phase transition in Pb0.99Nb0.02[(Zr0.6Sn0.4)1−xTix]0.98O3 (PNZST100x) antiferroelectric (AFE) ceramic system under the joint action of multi-physical factors, including composition, temperature, and electric field. Due to low energy barrier and enhanced zero-field entropy, the multi-phase coexistence point (x = 0.12) in the composition–temperature phase diagram yields a large positive EC peak of maximum temperature change (ΔTmax) = 2.44 K (at 40 kV/cm). Moreover, the electric field–temperature phase diagrams for four representative ceramics provide a more explicit guidance for EC evolution behavior. Besides the positive EC peaks near various phase transition temperatures, giant positive EC effects are also brought out by the electric field-induced phase transition from tetragonal AFE (AFET) to low-temperature rhombohedral FE (FER), which is reflected by a positive-slope boundary in the electric field–temperature phase diagram, while significant negative EC responses are generated by the phase transition from AFET to high-temperature multi-cell cubic paraelectric (PEMCC) with a negative-slope phase boundary. This work emphasizes the importance of phase diagram covering multi-physical factors for high-performance EC material design.